Enhancing psychiatric residency training through collaborative reflection on failures: a classroom action research on fostering growth mindset - Warut Aunjitsakul; Aimorn Jiraphan; Katti Sathaporn; Kanthee Anantapong (BMC Medical Education)
Abstract A growth mindset, positing intelligence as evolving rather than static, is pivotal in medical education, where errors are common and carry emotional repercussions. The “exhibition of failure (EoF)” classroom, aimed at residency trainees, employs reflective methods and group interventions to foster a growth mindset. This study utilizes classroom action research (CAR) to refine the EoF classroom process through two cycles conducted at University hospital, Thailand. Trainees shared failures and completed pre- and post-class questionnaires, including a mindset scale. Descriptive statistics and focus groups analyzed data, leading to adjustments in the classroom environment. Cycle I highlighted the importance of a safe, encouraging atmosphere and an appropriate schedule for sharing failure stories. Cycle II implemented changes such as maintaining a non-judgmental tone and adapting the schedule to trainee availability, resulting in improved mindset scores. Recommendations include consistent facilitators and specialized training. This CAR underscores the inevitability of failure experiences in medical settings, emphasizing their role in learning. The EoF classroom, comprising facilitated sessions, enhances trainee development and nurtures a growth mindset. It serves as a constructive tool for both medical trainees and staff, with trained facilitators essential for success. The study advocates for alternative approaches to promote cognitive flexibility and a growth mindset in medical education.